1987
DOI: 10.1063/1.338468
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between high-frequency Rayleigh wave attenuation and dc magnetoresistance in nickel thin films

Abstract: We present experimental data showing a correlation between the magnetic field dependence of the attenuation of 601.4-MHz Rayleigh-mode surface acoustic wave propagating through evaporated thin films of Ni and the dc magnetoresistance of these films. This correlation provides (1) a method for characterizing the magnetoelastic coupling between the Rayleigh waves and the films’ magnetic moment and (2) insight into the magnetic domain structure and anisotropy dispersion of these films which typically have uniaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The data correspond to the SAW transmission averaged over the FWHM of the central passband lobe |S 21 |. In addition to the hysteretic magnetization switching at |µ 0 H| < 3 mT already reported[13,14], two absorption maxima can be discerned as pronounced dips inFig. 2(b).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The data correspond to the SAW transmission averaged over the FWHM of the central passband lobe |S 21 |. In addition to the hysteretic magnetization switching at |µ 0 H| < 3 mT already reported[13,14], two absorption maxima can be discerned as pronounced dips inFig. 2(b).…”
mentioning
confidence: 66%
“…Since typical SAW frequencies range from a few MHz to several GHz, SAW-based RF spin-mechanics should enable the study of magnetization dynamics such as ferromagnetic resonance, driven only via RF elastic deformation, not via externally applied RF magnetic fields. The interaction of SAWs and ferromagnetic thin films has been studied experimentally by several groups [12][13][14][15]. Based on SAW magneto-transmission measurements with the static external magnetic field applied either perpendicular or parallel to the SAW propagation direction, these authors suggested that a magnetoelastic interaction most probably was the dominant interaction mechanism.…”
mentioning
confidence: 99%